Dry eye disease symptoms and quality of life in perimenopausal and postmenopausal women. (4th May 2021) - Garcia-Alfaro, P.; Garcia, S.; Rodriguez, I.; Vergés, C.
Abstract: Objective: This study aimed to evaluate dry eye disease (DED) symptoms and quality of life (QoL) in a group of perimenopausal and postmenopausal women, based on the Ocular Surface Disease Index (OSDI) questionnaire. Methods: An observational study was performed in a group of 1947 perimenopausal and postmenopausal women, aged between 45 and 79 years. The personal data collected were age, menopause status, age at menopause, and OSDI score. Results: The mean age of the group was 54.18 ± 6.84 years, with a mean age at menopause of 49.45 ± 4.02 years. The average OSDI score was 29.20 ± 19.4. The overall prevalence of DED symptoms was 79%, increasing significantly in postmenopausal women, 76.4% vs. 80.5% ( p = 0.029). In our group, 37.7% had severe DED symptoms. Ocular symptoms, vision-related functions, and environmental trigger scores were higher in postmenopausal women, leading to a lower QoL. The severity of OSDI score increases with age ( β coefficient: 0.15 [95% confidence interval: 0.02; −0.28]), while the severity of OSDI score decreases with a later onset age of menopause ( β coefficient: −0.27 [95% confidence interval: −0.55; −0.01]). Conclusions: DED symptoms are highly prevalent in perimenopausal and postmenopausal women. Postmenopausal women had a higher prevalence of symptoms and higher OSDI scores than perimenopausal women. The severity of DED symptoms and vision-related functions leads to poorer QoL.